Light-triggered, spatially localized chemistry by photoinduced electron transfer - Usgaonkar, S.; Deshmukh, S.; Biswas, B.; Karjule, N.; Yadav, P.; Nithyanandhan, J.; Kumaraswamy, G. (Angewandte Chemie-International Edition, 2019)
It is of immense interest to exert spatial and temporal control of chemical reactions. It is now demonstrated that irradiation can trigger reactions specifically at the surface of a simple colloidal construct, obtained by adsorbing polyethyleneimine on fluorescent colloidal particles. Exciting the fluorescent dye in the colloid affords photoinduced electron transfer to spatially proximal amine groups on the adsorbed polymer to form free radical ions. It is demonstrated that these can be harnessed to polymerize acrylic acid monomer at the particle surface, or to break up colloidal assemblies by cleaving a cross‐linked polymer mesh. Formation of free radical ions is not a function of the size of the colloid, neither is it restricted to a specific fluorophore. Fluorophores with redox potentials that allow photoinduced electron transfer with amine groups show formation of free radical ions.